Analisis Spasial Kerentan Fisik Bencana Banjir Menggunakan Metode Overlay - Wahyu Dzunaid Syawal; Uca Sideng; Amal Arfan (Jurnal Penelitian Pendidikan Geografi, 2025)
Makassar has been identified as one of the areas in South Sulawesi that experiences a high frequency of flood disasters. So, the aim of this research was to look at the flood vulnerability of the Makassar City from its physical aspect, namely consisting of rainfall, land slope, elevation, land use, river density, and also soil type. The data analysis technique in this research uses the overlay method with weighting and scoring of each physical aspect of flood vulnerability. The results of the research after carrying out the overlay technique showed that 8,053.84 hectares (47%) of the Makassar city area were in the very high vulnerability category, 7,901.40 hectares (42%) were in the high vulnerability category, then the area in the medium category was 1,741 hectares (10%), and 99.14 hectares (1%) are in the low category. The results of this study are expected to be a consideration for related parties to minimize the impact and risk of flooding and increase awareness of the potential for flooding in the Makassar City area.